Desert Island, Burrow, Grave : Wartime Hiding Places of Jews in Occupied Poland - Cobel-Tokarska, Marta (2018)
This book is an anthropological essay which aims to capture the elusive phenomenon of hideouts employed by Jews persecuted during the Second World War. Oscillating between life and death, the Jewish hideouts were a space of the most diverse and extremely complex human relations – a specific realm of everyday life, with its own inherent logic. Based on different literary sources, especially wartime and post-war testimonies of Jewish escapees, the author seeks to examine the realm of hideouts to develop a novel, interdisciplinary perspective on this often neglected aspect of the 20th-century history.